2008
DOI: 10.1016/j.ajic.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of methicillin-resistant Staphylococcus aureus and Acinetobacter baumannii in a long-term acute care facility

Abstract: Background-Patients in long-term acute care (LTAC) facilities often have many known risk factors for acquisition of antibiotic-resistant bacteria. However, the prevalence of resistance in these facilities has not been well described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
68
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 12 publications
4
68
0
Order By: Relevance
“…The article demonstrated that Acinetobacter baumannii is widespread including hospitals, long-term acute-care and nursing homes, and that the transfer of multidrugresistant strains among health care facilities is bidirectional. These data confirm previous report (Gould CV & Al, 2006;Saeed S & Al, 2006;Stephens C & Al, 2007;Furuno JP & Al, 2008) …”
Section: Others Organismssupporting
confidence: 83%
“…The article demonstrated that Acinetobacter baumannii is widespread including hospitals, long-term acute-care and nursing homes, and that the transfer of multidrugresistant strains among health care facilities is bidirectional. These data confirm previous report (Gould CV & Al, 2006;Saeed S & Al, 2006;Stephens C & Al, 2007;Furuno JP & Al, 2008) …”
Section: Others Organismssupporting
confidence: 83%
“…Traditionally, infections caused by Acinetobacter species were restricted to the intensive care unit (ICU) setting and to military personnel who have experienced combat-related injuries (6). More recently, these pathogens have spread to other locations in the hospital and to nonhospital populations and health care settings (1,6,7). Infections caused by A. baumannii are associated with devastating outcomes in terms of morbidity and mortality and contribute to high hospital costs.…”
mentioning
confidence: 99%
“…A cinetobacter, a Gram-negative coccobacillus, has become a frequent pathogen in hospitals and other health care settings (1,2). Found naturally in soil, these bacteria remain stable even under extreme conditions of temperature, humidity, and pH and in the presence of commonly used detergents, such as highly concentrated alcohol preparations, and other antiseptics that normally inhibit the growth of other bacteria (3).…”
mentioning
confidence: 99%
“…ethicillin-resistant Staphylococcus aureus (MRSA) prevalence in nursing homes often exceeds that in acute care settings, including intensive care units (2)(3)(4)39). The MRSA burden may be high because nursing home residents have multiple comorbidities, chronic wounds, frequent exposure to antibiotics, and require health care worker contact to perform activities of daily living (ADL) (2,5,6).…”
mentioning
confidence: 99%